Relationship and driving factors between urbanization and natural ecosystem health in China. (March 2023) - Liu, Ranran; Dong, Xiaobin; Wang, Xuechao; Zhang, Peng; Liu, Mengxue; Zhang, Ying
Graphical abstract: Highlights: Ecosystem health (EH) and urbanization of the 260cities of China were assessed. Urbanization and EH have been significantly and slightly improved respectively. Urbanization mainly affected EH by changing the demand for ecosystem services. The urban development type was mainly the medium-level balanced. The drivers of the coupling relationship were explored using a Geodetector. Abstract: Sustainable urban development is one of the most urgent problems worldwide, especially in China, which is in rapid urbanization. Reducing the negative impacts of urbanization and improving the relationship between the two have become research priorities. Using 260 cities in China as the research object, this study evaluated the level and temporal and spatial variation of urbanization and natural ecosystem health, explored the relationships between them, and influence mechanism of urbanization on natural ecosystem health. The results showed that the level of population urbanization, social urbanization, economic urbanization and land urbanization was significantly improved in 2000 compared to 2015, and the spatial distribution was higher in the east of China than in the west. The overall level of ecosystem health improved slightly throughout the same period, and its spatial distribution was higher in the north of China than in the south. In terms of the four dimensions of ecosystem health, the ecosystem services and organization were improved, and the ecological environment and elasticity were decreased. Urbanization mainly affected ecosystem health by changing the demand for the quantity and type of ecosystem services through the growth and aggregation of population. However, under the comprehensive effect of the four dimensions of urbanization on natural ecosystem health, the overall constraint intensity of urbanization on natural ecosystem health was relatively stable. The coupling and coordination level between urbanization and natural ecosystem health showed improvement from 2000 to 2015, and the social and economic factors were highly influential. According to the level of urbanization and natural ecosystem health, all cities were classified, which showed the urban development was mainly the medium-level balanced. On this basis, management suggestions were put forward for each type of city. By analyzing the action process and mechanism between urban development and natural ecosystem health, it provides a theoretical basis for in-depth understanding and coordinating the relationship of the urban ecological economy.